Daya Saing Kawin Jantan Mandul Aedes albopictus: Uji Semi Lapang untuk Pengendalian Vektor Demam Berdarah Dengue (DBD) - Retno Hestiningsih; Muhammad Iqbal Kurniawan; Martini Martini; Nissa Kusariana; Bagoes Widjanarko; Ali Rahayu (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Aedes albopictus is the secondary vector that played an important role in the transmission of Dengue Haemorrhagic Fever (DHF). Previous research has examined the exact radiation dose in producing Ae. albopictus sterile males, which is a dose of 60 Gy. Before being applied in the field, a semi-field trial phase is actually needed. This study aims to determine the competitiveness of Ae. albopictus sterile male mating with a semi-field test. This study is a field experiment and used males radiated until becoming a sterile mosquito. Subject mated to fertile female and divided into 3 groups of samples, the control group (10 normal males and 10 normal females), the test group (10 sterile males and 10 normal females) and the combination group (10 normal males, 30 sterile males, and 10 normal females). Treatment was performed with 3 replications. Tested mosquitoes were placed into the special tent of bugs (bugdoom) with condusive environmental conditions of Ae. albopictus mosquitoes. The results of study showed that there was significant differences (p ≤ 0.0001) the level of sterility of eggs. The test insect group produced the highest sterile eggs 100% compared to the other groups. Value of Mating Competitiveness (C index) Male Sterile Mosquito Ae. albopictus of 0.34. This showed that for TSM applications in actual conditions, it is required 3 times of the population size of sterile males from the normal male population in the field.